AB0329 Clinical effectiveness and infection rate in rheumatoid arthritis patients switched from anti-tnf agents to abatacept. (23rd January 2014) - Pietrosanti, M.; Di Rosa, R.; Salemi, S.; Markovic, M.; Carusi, V.; Biondo, M. I.; Catoni, M.; Laganà, B.; Sorgi, M. L.; D'Amelio, R.
Abstract : Background: Increased risk of infection is an important safety concern in Rheumatoid Arthritis (RA) patients receiving biological therapies. Previous reports suggest a more favourable safety profile for Abatacept (ABT) respect to anti TNF. Objectives: The aim of our study is to compare the incidence of mild/moderate and serious infections in a group of RA patients switched from anti-TNF agents, to ABT. Methods: From 2008 to 2012 19 patients previously treated with anti-TNF agents, switched to ABT for inefficacy or adverse events. 6/19 patients (31%) were previously treated with more than one anti-TNF agent. We used the Chi-Square test to evaluate incidence of infections during prior therapy with anti-TNF compared with incidence of infections occurred with ABT. T test was used to test effectiveness of ABT at T0 and T6 analyzing DAS 28 and HAQ. Results: Incidence of infections during previous treatment with anti-TNF agents was not statistically different from what observed during ABT treatment (p< 0, 2). We observed significant improvement in the disease activity between T0 and T6 according to DAS 28 (p< 0, 002). Moreover the difference between HAQ T0 and T6 supported improvement of disease activity, although statistically non significant (p< 0, 06). Conclusions: RA patients under both ABT and anti-TNF agents treatment are susceptible to infections, nevertheless the incidence of infections results unchanged. ABT effectiveness was improved from T0 to T6, demonstrating the favourable effect of switching to ABT in patients with RA previously failing anti-TNF agents. Disclosure of Interest: None Declared